Neurilemmoma of the ciliary body: report of a case. Issue 9 (September 1983) - Rosso, R; Colombo, R; Ricevuti, G
Abstract : A case of ciliary body neurilemmoma is described. This neoplasm is extremely rare in the uveal tract and has been reported only once in the ciliary body. After extensive clinical studies of the rapidly growing tumour enucleation was performed. Subsequent histological examination showed typical features of highly vascular benign neurilemmoma. The main clinical and pathological features are reported and diagnostic problems are discussed.